Life threatening effects of synthetic cannabinoids: 3 cases - Özer, Ürün; Uzun, Utku; Turan, Bahadır; Çarpar, Elif (Journal of Dependence, 2015)
In recent years, new psychoactive substances, known as designer drugs, have gained in popularity and synthetic cannabinoids have risen to prominence among them. Because they are often difficult to detect in laboratory tests, and due to their dynamic and unforeseeable structures, data related to their effects is limited. In this article, three separate subjects who developed toxic hepatitis, loss of consciousness and cardiopulmonary arrest, respectively, following synthetic cannabinoid use, are presented. Additionally, life threatening physical effects of synthetic cannabinoids are discussed.All three cases were admitted to the psychiatric emergency unit with psychiatric symptoms. Following revelation of the use of synthetic cannabinoids, in their follow-up serious physical signs such as toxic hepatitis had developed. These life-threatening signs resulted in loss of consciousness in the second case and cardiopulmonary arrest and eventual death of the third patient. Benzodiazepine was detected in the urine toxicology screen in only one of the cases. In the other cases, urine toxicology was negative. Emergency laboratory test findings were remarkable with creatine kinase elevation and impairment in liver function tests.Our cases are important to demonstrate the life threatening conditions related to synthetic cannabinoid use. Having stronger effects than natural cannabis, combined with its low cost, easy accessibility, and being difficult to detect in standard toxicology tests has made the preference of synthetic cannabinoids an increasing trend. Awareness of these substances and the manifestations related to their use would benefit clinicians in the diagnosis, treatment, and follow up of these patients and help to prevent the overlooking of risky situations.
Keywords: Synthetic cannabinoid; toxic hepatitis; cardiopulmonary arrest